Portuguese intermunicipal organization - Basic principles - Rui Alves (European Regional Science Association (ERSA), 2004)
Portuguese territorial organization has two levels of territorial decision support legitimated: central and local/municipal government (municipalities). The lack an intermediate level of support decision between those levels is a central problem on territorial decision support system. Intermunicipal organization level can it play an important role as an intermediate level of decision-making process. After rejection of the regionalization process in 1998, trough popular referendum, Portuguese government has approved two laws of the Public Administration Framework Reform - Metropolitan Areas Act and Intermunicipal Organization Act (13th May 2003). Metropolitan Areas Act establishes two ways to promote the intermunicipal organization among municipalities: Great Metropolitan Areas (more than 350 000 inhabitants) and Urban Communities (more than 150 000 inhabitants). Intermunicipal Organization Act also establishes two ways to promote the intermunicipal organization between at least two municipalities: Intermunicipal Communities of wide Scope and Intermunicipal Communities of Specific Scope. This paper aims to present and discuss a set of basic principles towards success of this reform, and at the same time, to present some results of the research developed by the author of the paper.
Keywords: 330